PENGARUH PERSEPSI PELAKSANAAN SENSUS PAJAK NASIONAL DAN KESADARAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DI LINGKUNGAN KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK DAERAH ISTIMEWA YOGYAKARTA - Rinta Mulia Dewinta; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2012)
This study aims to analyze factors that influence tax compliance in the Regional Tax Office Special Region of Yogyakarta. Research desain is survey research using questionnaire as instrument. The respondents of this research are taxpayer’s especially business owners who are in the business district, high-rise building or office and have stickers of Sensus Pajak Nasional. This research use the perception of Sensus pajak Nasional and tax awareness as independent variable on taxpayer’s compliance as dependent variable. Data analysis was performed using multiple linear regression analysis with SPSS 20.00 for windows. The findings of this research show that, the effect of : (1) perception of Sensus pajak Nasional on taxpayer’s compliance is positive and significant. (2) tax awareness on taxpayer’s compliance is positive and significant.